1988
DOI: 10.1093/jac/21.suppl_d.101
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of erythromycin acistrate and erythromycin stearate in acute skin infections of patients with atopic eczema

Abstract: The efficacy and tolerability of a new erythromycin derivative, erythromycin acistrate (EA), were compared with that of erythromycin stearate (ES) in 42 patients with infected atopic eczema. The dosage of EA was 400 mg tid and that of ES 500 mg tid. The duration of treatment ranged from five to 12 days. The patients were hospitalized and evaluated before treatment and on the last day in hospital. The infective pathogen was usually Staphylococcus aureus in both groups. Without local antibacterial treatment both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…In spite of growing concern about rising resistance rates, erythromycin is still one of the mainstays of therapy for this indication (4, 14, 15). Recent reports from worldwide antimicrobial surveillance programmes indicated that between 49 (USA, 16), 38 (Europe, 17) and 24% (Asia, 18) of all S. aureus strains are now resistant to erythromycin.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of growing concern about rising resistance rates, erythromycin is still one of the mainstays of therapy for this indication (4, 14, 15). Recent reports from worldwide antimicrobial surveillance programmes indicated that between 49 (USA, 16), 38 (Europe, 17) and 24% (Asia, 18) of all S. aureus strains are now resistant to erythromycin.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, erythromycin-A 2′-ethylsuccinate is used as an oral suspension in children to reduce the unpleasant taste of the drug. Topical therapy of acute skin infections in patients with atopic eczema, with both ERY acistrate and ERY stearate, was able to eradicate the infection due to S. aureus in more than 60% of cases (7).…”
Section: Introductionmentioning
confidence: 99%
“…Although its half-life in plasma is short and the pharmacokinetic (PK) profile intraindividually heterogeneous, it is very well distributed throughout body tissues and accumulates in leukocytes (11). While clinical studies have shown the effectiveness of erythromycin in skin and soft tissue infections (33,39), the in vivo penetration and the resulting free concentrations in interstitial space of soft tissues, i.e., the most important site of bacterial infections, have not been reported until now. High cellular uptake, relatively short retention, and fast back release from white blood cells (WBCs) are considered important properties of the PK of erythromycin (1).…”
mentioning
confidence: 99%